Factors influencing the compliance of taxpayers - Meidawati, Neni; Azmi, Muhammad Nurul (Journal of Contemporary Accounting, 2019)
The compliance in tax reporting of an individual taxpayer who is running business or having freelance job is one of the ways to maximize the tax revenue in Indonesia. This research aims to examine the factors that affect the tax reporting compliance of an individual taxpayer who is running business or having freelance work. The data were collected by distributing questionnaires. The regression model used in this study was multiple linear regression using SPSS. The sampling method was random sampling which involved 47 individual taxpayers who were already registered at Tax Service Office (KPP) Pratama Pontianak with an error rate of 5%. The result showed that level of awareness had positive and significant influence on tax reporting compliance of the individual taxpayers at KPP Pratama Pontianak who are running business and doing freelance work. Meanwhile, tax knowledge and tax sanction had no effect toward tax reporting compliance of the individual taxpayers running business and doing freelance work.